Assessment of the Effects of Global Postural Re-Education on Musicians with Nonspecific Musculoskeletal Pain as Assessed by Questionnaires and Infrared Thermography - Mercado, Dapne (Université d'Ottawa / University of Ottawa, 2018)
Background: The Global Postural Re-education (GPR) method seems to be an effective method for the treatment of musculoskeletal disorders. However, no study has examined its effects on a group of musicians with musculoskeletal pain. Additionally, infrared thermography (IRT) has been widely used in the field of medicine as a monitoring a diagnostic tool, which can provide empirical data about the effectiveness of the GPR method. Objective: To examine the effects of GPR using scales and questionnaires and IRT. Methods: This thesis enclosed two articles. In the first, musicians with (N=6) and without (N=6) musculoskeletal pain underwent a thermographic evaluation to examine the skin temperature asymmetry (STA) between both groups as a representation of musculoskeletal pain. The second article was a randomized control trial and examined the effects of the GPR on a group of 13 participants with musculoskeletal pain (7 experimental, 6 controls) after receiving 8 sessions of GPR. Pain, disability and quality of life data was collected using the VAS, MPIIQM, SF-36. A thermographic assessment was also conducted to examine the correlation between pain severity and degree of STA, and changes in contralateral skin asymmetries before and after the intervention. Results: The first article revealed no significant differences in STA between groups. Results from the second article showed statistical significant improvements in pain, disability and quality of life on the group who received the GPR intervention. Results from the IRT analysis were not significant. Conclusion: Results from the self-report questionnaires suggest that GPR is effective in treating musculoskeletal pain in the targeted group of musicians. Pain changes did not correlate with thermal outcomes. Further studies are needed to confirm the results obtained with IRT.
Keywords: Global Postural Re-education; Musicians; Infrared thermography; Physiotherapy